2020
DOI: 10.1130/g47614.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assembly of high-Mg andesites and dacites by magma mixing at a continental arc stratovolcano

Abstract: Studies of pre-eruptive processes at active volcanoes require precise petrochronological constraints if they are to contribute to hazard assessment during future eruption events. We present petrological and geochemical data and orthopyroxene diffusion time scales for samples from Late Pleistocene high-Mg andesite-dacite lavas (Mg# 53–69) at Ruapehu volcano, New Zealand, as a case study of rapid magma genesis and eruption at a continental arc stratovolcano. Assembly of Ruapehu high-Mg magmas involved the mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Their erupted products span the so-called andesitic magmatic suite, ranging from basaltic andesite to rhyolite. The occurrence of repeated pre-eruptive mixing events involving andesitic and dacitic melts is often recognized in the discharged magmas [e.g., (Tamura et al, 2003;Shane et al, 2008;Conway et al, 2020)].…”
Section: Applications To Magma Mixing Dynamicsmentioning
confidence: 99%
“…Their erupted products span the so-called andesitic magmatic suite, ranging from basaltic andesite to rhyolite. The occurrence of repeated pre-eruptive mixing events involving andesitic and dacitic melts is often recognized in the discharged magmas [e.g., (Tamura et al, 2003;Shane et al, 2008;Conway et al, 2020)].…”
Section: Applications To Magma Mixing Dynamicsmentioning
confidence: 99%
“…As a result, Ruapehu has erupted more dacite magmas than Tongariro due to extensive crustal assimilation and fractional crystallisation through a central magma plumbing axis. Ruapehu typically shows evidence for magma mixing resulting from the interaction between recharging and stalled magmas (sometimes directly leading to eruption: Conway et al 2020). At Tongariro, the extension rate is greater, the volcano is traversed by several faults parallel to the Taupo Rift orientation and cone building has occurred over a wider area, leading to a less unified edifice without a central focus.…”
Section: Discussionmentioning
confidence: 99%
“…In the SiO 2 versus MgO plot (Figure 13C), the bulk of data from both volcanoes form an overlapping array, but a high-Mg suite, dominated by Ruapehu samples (Conway et al 2018), runs subparallel to this array. Ruapehu high-Mg lavas were generated by influx of mantle-derived mafic magmas with entrained primitive olivines, which rapidly hybridised with mid-crustal felsic magma bodies prior to their eruption (Conway et al 2020). Like TAS diagrams, K 2 O versus SiO 2 data (Figure 13D) show overlapping Tongariro and Ruapehu arrays, but with Ruapehu samples extending to higher values.…”
Section: Magma Systemsmentioning
confidence: 94%
“…Studies on the Ruapehu magmatic system in New Zealand have also reported different storage pressures and depths using melt inclusions and geobarometers. Kilgour et al (2014) reported melt inclusion entrapment pressures of 0.5-3 kbar and depths of c. 2-9 km; whereas mineral-based geobarometry estimates by Conway et al (2020) report pressures of 3.6 kbar and depths of c. 13 km. These studies highlight that differences in pressure and depths of crystallisation can be obtained using different methods, which can have a significant influence on the interpretation of the magmatic system.…”
Section: Discrepancy Between Melt Inclusion and Geobarometric-derived Crystallisation Pressures And Depthsmentioning
confidence: 99%